A high-plasticity hot-rolled carbon wire rod for 1670MPa bridge cables and a manufacturing method thereof
By using hot-rolled carbon wire rods with a C-Si-Mn composition in wire rods for bridge cables, combined with online molten salt weak quenching isothermal treatment technology, a mixture of tempered sorbite and tempered bainite is formed. The structure solves the problems of high material cost and insufficient plasticity, achieves high strength and high plasticity, and reduces the risk of wire breakage and torsion fracture during drawing.
Patent Information
- Application Number
- CN202411356386.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
While improving the initial strength, the existing 1670MPa-grade bridge cable coils have high material costs, insufficient plasticity, and difficult to take into account both the structural uniformity and tensile resistance, which is prone to the risk of drawing and breaking of wires and torsion.
Adopt hot-rolled carbon carbon-based components based on C-SI-MN, and uses temperature treatment such as the weak quenching of online salt salt, so that the dish bars are cooled at high cold speed to the mixed with the soma and the bellite phase area. The phase area forms a hybrid tissue dominated by the rebounding sorcem and the backburnex, which regulates the uniformity of the tissue and the strong plastic performance.
It significantly reduces the material cost, improves the plasticity and structural uniformity of the wire rod, reduces the risk of wire breakage and torsion fracture, and meets the high strength and high plasticity requirements of 1670MPa bridge cables.
Smart Images

Figure CN118854174B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods for bridge cables, and specifically relates to a high-plasticity hot-rolled carbon wire rod for 1670MPa-grade bridge cables and a manufacturing method thereof. Background Art
[0002] As the main load-bearing structure of cable-stayed bridges, suspension bridges, and drawbridges, bridge cables often have to bear static and dynamic loads under environmental stresses such as rivers, lakes, and seas for a long time. The use environment is extremely harsh. The wire rods used for bridge cables are used as the base material, which plays a leading role in the performance of bridge cables. Compared with the drawing and manufacturing of cold-headed steel wire rods, the wire rods used for bridge cables need to undergo deep cold drawing deformation with a larger reduction rate, and the plastic loss is greater during the process. Compared with the wire rods used for stranded wires, the wire rods used for bridge cables often need to be galvanized after deep drawing into steel wires. Hot-dip galvanizing will lose the strength of the wire rods to a certain extent, and then there are strict torsion tests and fatigue performance tests. Therefore, bridge cables have high requirements for the cold workability, initial strength, and same-circle difference of the wire rods. Producing hot-rolled wire rods with higher plasticity and uniform organization is of great significance to reducing the risk of wire breakage during the drawing process of bridge cable manufacturing and improving the yield rate.
[0003] In order to improve the initial strength of 1670MPa grade bridge cable wire rod in the prior art, a strong hardenability element strengthening system such as Cr and B is added to the high carbon steel composition, and microalloying elements such as V, Ti, and Nb are added to refine the grains and strengthen the wire rod. The wire rod is made into pearlite steel on the Stelmor air-cooling line after spinning. For example, the 1670MPa grade bridge cable galvanized steel wire rod and its preparation method disclosed in patent CN102181786A are adjusted to a C-Si-Mn-Cr-V component system on the basis of 82B steel grade, and B, Ti, etc. can be selected. Combined with the Stelmor fast-then-slow air cooling after spinning, the wire rod is made into a wire rod with a high sorbite content, achieving a tensile strength of more than 1200MPa and a surface reduction rate of more than 35%; Therefore, the 1670MPa grade bridge cable wire rod with lower manufacturing cost, higher plasticity and uniform organization still has the following technical difficulties:
[0004] 1. Although the addition of Cr, micro-alloy elements and other components improves the strength of wire rod, the price is relatively high, which will increase the production cost of wire rod and lose its plasticity and toughness. Reducing the alloy content or eliminating the alloy component for the purpose of reducing costs will lead to a significant loss of strength. When manufacturing bridge cables, a larger reduction rate is required to increase the strength by drawing. Therefore, the initial specifications and plasticity loss of wire rod are relatively large, which is more likely to cause wire breakage during drawing and affect the torsional performance of the steel wire.
[0005] 2. The increase of carbon content will aggravate segregation. On this basis, when the high-temperature wire rod after spinning is processed by the Stelmor air cooling line, the maximum cooling rate is only 10℃ / s, which will aggravate the precipitation of tertiary cementite along the grain at 700~800℃ in the process of controlled cooling. The carbide of cementite will coarsen, affecting the strength and plasticity properties, and even causing secondary cementite network precipitation due to segregation, increasing grain boundary brittleness, and seriously deteriorating plasticity and toughness properties and organizational uniformity. Reducing the carbon content for the purpose of reducing the adverse effects of cementite will not only cause strength loss, but also due to limited cooling control ability, the wire rod will pass through the precipitation temperature range of tertiary cementite for a long time, and the organizational uniformity and plasticity cannot be significantly improved, which will cause wire breakage during drawing and the torsional performance of steel wire is difficult to guarantee.
[0006] 3. In order to minimize the formation of network cementite, rapid cooling is used before and in the early stage of phase transformation to form a fine organizational structure. However, as the wind cooling intensity of the Stelmor air-cooled line increases, the wind direction and air volume cannot be controlled, and a significant temperature difference will occur between the windward side and the leeward side of the wire rod. The untransformed austenite structure in the organization is easily transformed to form abnormal bainite or martensite structure. The risk of abnormal tissue precipitation increases and its precipitation will significantly deteriorate the cold working performance of the wire rod, making it difficult to control the uniformity of the wire rod organization, and the difference in mechanical properties increases, aggravating the risk of wire breakage during drawing.
[0007] 4. During the air cooling process of the wire rod after phase transformation, the precipitation of abnormal tissue is uncontrollable. The increase in carbon content makes the tissue lamella thicker. At the same time, the wire rod is in a low-temperature state due to continuous cooling after being incubated with troostite tissue, lacking thermal power, resulting in high residual stress inside the wire rod. The uneven distribution of residual stress will further increase the fluctuation of mechanical properties, and the troostite tissue itself has a high density dislocation, which will make the final wire rod insufficient in plasticity, severe work hardening during the drawing process, a sharp drop in plastic toughness, and difficulty in guaranteeing the torsional performance of the steel wire. The decrease in the troostite content in the tissue or the increase in the lamella spacing and the increase in the proportion of ferrite will further deteriorate the drawing performance and mechanical properties, affecting the performance of the bridge cable. Summary of the invention
[0008] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-plasticity hot-rolled carbon wire rod for 1670MPa-level bridge cables and a manufacturing method thereof, which can appropriately reduce material costs, make the microstructure phase change more controllable, avoid abnormal martensitic structure, regulate microstructure uniformity, and significantly improve the plasticity of the wire rod while taking into account the strength of the wire rod. The wire rod is suitable for the manufacture of 1670MPa-level bridge cables and reduces the risks of wire breakage and torsional fracture during deep drawing.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] A method for manufacturing a 1670MPa-grade high-plasticity hot-rolled carbon wire rod for bridge cables, the manufacturing method comprising:
[0011] The wire rod is produced by rolling according to the chemical composition of the hot-rolled carbon wire rod, wherein the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.69%~0.74%, Si: 0.3%~0.45%, Mn: 0.65%~0.8%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into a wire rod at a spinning temperature of ≥890°C, and then is isothermally quenched by online molten salt. The wire rod is cooled at a cooling rate of ≥33°C / s to a mixed phase region of troostite and bainite to form a mixed structure mainly composed of troostite and bainite, and isothermal tempering transformation is performed. Finally, it is slowly cooled by a roller to form a hot-rolled carbon wire rod with a microstructure including 47% to 53% tempered troostite by volume, 40% to 46% tempered bainite by volume, and the rest being a mixed structure composed of ferrite and fused troostite.
[0012] The chemical composition and mass percentage design basis of the above hot rolled carbon wire rod include:
[0013] (1) Carbon: C is the most economical and effective element to ensure that the wire rod can obtain high strength. Increasing the C content can expand the austenite phase region, reduce the bainite start transformation temperature, and enable the bainite reaction to proceed at a lower temperature. During the bainite phase transformation, a large number of dislocations can capture carbon atoms and use the pinning dislocations to strengthen the wire rod strength, which can make up for the loss of alloying elements. However, too high a C content will lead to an increase in component segregation during the solidification process of the alloy, reduce the martensite start transformation temperature, and increase the risk of abnormal structures such as martensite. Therefore, in order to take into account the high-strength performance of 1670MPa-level bridge cables and the regulation of wire rod structure, the carbon content is appropriately reduced. On the one hand, it can reduce component segregation. Combined with the wire rod after spinning, it is subjected to The online molten salt weak quenching isothermal treatment can further reduce the risk of network carbide precipitation, and inhibit the peak precipitation of tertiary cementite, thereby refining cementite carbides and improving organizational uniformity. On the other hand, it can reduce component segregation and regulate the phase transformation peak temperature of austenite to troostite or bainite, so that the high-temperature wire rod can directly undergo the online molten salt weak quenching isothermal treatment, which can not only improve the precipitation of tertiary cementite, but also stably enter the mixed area of troostite phase transformation temperature range and bainite phase transformation temperature range, which is more convenient for regulating the proportion of troostite and bainite, avoiding abnormal martensite organization, maximizing the strengthening effect of carbon element, and improving organizational uniformity; therefore, the mass percentage of C is controlled to be 0.69%~0.74%.
[0014] (2) Silicon: Si is often used as a deoxidizer during smelting to remove excess oxygen in molten steel to prepare qualified steel billets. At the same time, silicon can improve the solid solution strength of austenite, the critical transformation temperature of steel and the activity of carbon, accelerate the diffusion of carbon, and will not slow down the phase change rate, avoiding carbon aggregation, thereby achieving the purpose of refining the formation of troostite and bainite structures during online molten salt weak quenching isothermal treatment. However, excessive silicon will increase the graphitization tendency of C, causing austenite residues, which strongly affects the subsequent galvanizing process. Therefore, in order to take into account the high strength and toughness of steel wire rods for bridge cables and facilitate the regulation of wire rod structure, the mass percentage of Si is controlled to be 0.3%~0.45%.
[0015] (3) Manganese: Mn is often used as a deoxidizer during smelting to remove excess oxygen in the molten steel. At the same time, it converts S in the molten steel into MnS to reduce hot brittleness and ensure the smooth progress of the rolling process. It can use solid solution strengthening to increase the strength and wear resistance of the wire rod, thereby improving the mechanical properties of the bridge cable steel wire. However, when the Mn content is too high, it will aggravate the segregation during the solidification process of the steel billet, causing grain growth and uneven composition, delaying the start of bainite phase transformation and prolonging the completion time of the phase transformation, slowing down the diffusion rate of C, and being unfavorable for controlling the proportion of tempered bainite and tempered bainite during online molten salt weak quenching isothermal treatment. Therefore, in order to take into account the high strength and toughness combination of steel wire rods for bridge cables and facilitate the control of wire rod structure, the mass percentage of Mn is controlled to be 0.65%~0.8%.
[0016] (4) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0017] In the above manufacturing method, the high carbon carbon component rolling production line based on C-Si-Mn does not add strong hardenability components such as Cr and B, and micro-alloy components such as V and Ti compared to the existing wire rod, which can reduce material costs, and optimize the C, S, and Mn ratio to control the phase transformation peak temperature of troostite or bainite, in preparation for process control, and directly enters the salt bath after high-temperature spinning for online molten salt weak quenching isothermal treatment:
[0018] First, compared with the existing Stelmor air cooling after spinning, which often weakens the strengthening effect of carbon due to the limited cooling rate during the cooling phase change process, the present invention can utilize the high heat exchange capacity of molten salt to cool the wire rod at an extremely fast cooling rate, quickly skip the secondary cementite precipitation temperature range, avoid the adverse effect of network carbide on the plasticity of the wire rod, and at the same time inhibit the peak precipitation of tertiary cementite at 700-800°C to avoid its large-scale precipitation causing intracrystalline brittleness and unevenness, thereby refining cementite carbides, effectively improving the utilization value of carbon elements, and improving the overall strength and plasticity of the wire rod.
[0019] 2. Compared with the existing Stelmor air cooling treatment after spinning, the uncontrollable cooling rate of the wire rod during the cooling phase transformation often leads to the production of abnormal structures such as martensite. After appropriately reducing the carbon content, the segregation of the wire rod can be further improved. With the high spinning temperature and rapid cooling of the molten salt, a large degree of supercooling is formed. While suppressing the tertiary cementite, the wire rod can be promoted to quickly enter the mixed phase region of the troostite phase region and the bainite phase region in the high-temperature austenite state. The troostite lamella spacing formed by the phase transformation is finer, which is beneficial to providing matrix strength and reducing the difficulty of isothermal tempering. The bainite formed by the phase transformation has higher strength than the troostite, which can be combined to provide matrix strength to compensate for the strength loss caused by reducing carbon content and eliminating alloy elements. At the same time, when the wire rod passes through the molten salt, the molten salt is wrapped on the surface of the wire rod for uniform heat transfer, and there is no temperature difference problem between the windward side and the leeward side. The mixed phase transformation of troostite and bainite can be controlled, effectively avoiding the risk of abnormal structure precipitation such as martensite caused by high C element, and further improving the uniformity of the structure.
[0020] 3. Compared with the existing Stelmor air cooling treatment after spinning, it is difficult to adjust the strength-plasticity matching of the wire rod due to the continuous cooling of the wire rod during the cooling phase transformation process. The wire rod can be kept consistent with the molten salt temperature after online molten salt weak quenching isothermal treatment, and a longer isothermal treatment is carried out in the mixed phase area of troostite and bainite instead of continuous cooling. On the one hand, long-term treatment in the mixed phase area promotes the transformation of high-temperature austenite in the wire rod to troostite and bainite, and adjusts the proportion of troostite and bainite to form a mixed structure dominated by troostite and bainite, reduce the ferrite content, and avoid adverse effects on the matrix strength. Sufficient transformation also prevents the wire rod from forming abnormal structure in the subsequent roller slow cooling process due to residual austenite, so that the structure control and uniformity can be guaranteed; on the other hand, compared with Continuous cooling can keep the wire rod in a high-temperature isothermal state for a longer time, giving more thermal power to the tempering of the structure, promoting the melting of the bainite structure and its transformation to spheroidization to form fused bainite and tempered bainite structures, reducing the structure stress and quenching density, to improve the influence of the bainite structure on the drawing hardening during the manufacturing of bridge cables. Compared with the traditional method of treating the bainite structure as a hard and brittle phase abnormality, it can promote the bainite structure to reduce the dislocation density and become a tempered bainite structure. The tempered bainite can retain the high-strength characteristics of bainite and effectively improve the plasticity to obtain a strong and tough structure, thereby utilizing the bainite structure and significantly improving the plasticity of the wire rod by regulating the tempering state. At the same time, this molten salt treatment regulation method in the mixed phase zone also makes the process relatively simple, which is beneficial to improving production efficiency on the basis of controllable structure.
[0021] The wire rod is subjected to online molten salt weak quenching isothermal treatment and then roller slow cooling, which can continue the high temperature state of the wire rod, and further use the slow cooling treatment to promote the tempering softening of the matrix structure and the micro-spheroidization of some structures, and carry out continuous softening, ultimately achieving the wire rod structure regulation and strength-plastic performance matching, and the uniformity of the wire rod structure is effectively improved.
[0022] In a preferred embodiment, during the rolling, the initial rolling descaling water pressure after the steel billet leaves the heating furnace is controlled to be ≥18MPa, and high-pressure water can be used to descaling the surface of the steel billet leaving the heating furnace to avoid the oxidized surface being left in the subsequent rolling process and damaging the surface quality of the wire.
[0023] Since the wire laying temperature is relatively high, the limitation of low-temperature wire laying on low-temperature rolling can be avoided. A higher rolling temperature is selected to promote the homogenization of wire rod composition, reduce the load on the rolling mill and the deformation resistance of the wire rod. With appropriate initial rolling, intermediate rolling reduction and a larger final rolling reduction, it is helpful to promote the dynamic recrystallization of the wire rod, refine the grain structure, and strengthen the matrix. In a preferred embodiment, during the rolling, the initial rolling temperature is 1050~1090℃, the initial rolling reduction is 26%~36%, the intermediate rolling temperature is 960~1010℃, the intermediate rolling reduction is 26%~30%, the final rolling entrance is 910~940℃, and the final rolling deformation is 25%~35%.
[0024] In a preferred embodiment, the molten salt temperature of the online molten salt weak quenching isothermal treatment is 450~490℃, and the treatment time is 450~750s. This molten salt temperature range is in the mixed temperature interval of the wire rod troostite and bainite phase transformation. The lower the molten salt temperature and the longer the treatment time, the temperature shifts toward the bainite peak phase transformation temperature, the proportion of tempered bainite in the wire rod increases, the proportion of tempered troostite decreases, the strength of the wire rod increases, and the plasticity decreases. However, if the molten salt temperature is too low, it is not conducive to the troostite transformation and isothermal tempering. If the treatment time is too short, the austenite structure is not fully transformed, which is not conducive to abnormal structure control and matrix softening. On the contrary The higher the molten salt temperature and the longer the treatment time, the temperature shifts toward the troostite peak phase transformation temperature, which can provide more thermal power for isothermal tempering. The proportion of tempered troostite in the wire rod increases, and the proportion of tempered bainite decreases. The strength of the wire rod decreases and the plasticity increases. However, if the molten salt temperature is too high, it will be unfavorable for the bainite phase transformation and even the formation of troostite with finer interlamellar spacing and the control of ferrite formation. If the treatment time is too long, the energy consumption will increase and the wire rod will be too soft, which is not conducive to efficient production and matrix strength. Therefore, the molten salt temperature and treatment time can be further controlled to make the proportion of tempered troostite and tempered bainite more controllable and adjust the strength-plasticity matching of the wire rod.
[0025] In a preferred embodiment, the molten salt circulation rate of the online molten salt weak quenching isothermal treatment is 500~640t / h, and the molten salt temperature rise is ≤9°C. Selecting a larger molten salt circulation rate to control the molten salt temperature rise can improve the processing accuracy of the online molten salt weak quenching isothermal treatment, which is beneficial to reducing the risk of abnormal tissue and regulating tissue uniformity.
[0026] In a preferred embodiment, the roller slow cooling controls the wire rod to be cooled at a cooling rate of 0.2-0.5°C / s until it is coiled. At this cooling rate, the wire rod can be continuously softened at high temperature, further improving the plasticity of the wire rod.
[0027] In a preferred embodiment, the roller slow cooling adopts a closed insulation cover, and the wire rod is transported into the insulation cover at a roller speed of 0.2~0.5m / s. The cooling speed and rapid production are ensured with an appropriate roller speed. When the production environment temperature is low, the hot air generated during the online molten salt weak quenching isothermal treatment can also be introduced into the insulation cover to further control the slow cooling.
[0028] A high-plasticity hot-rolled carbon wire rod for 1670MPa-grade bridge cables, wherein the hot-rolled carbon wire rod is manufactured according to any of the above-mentioned methods for manufacturing high-plasticity hot-rolled carbon wire rod for 1670MPa-grade bridge cables.
[0029] The hot-rolled carbon steel wire rod is based on the high carbon component of C-Si-Mn, and has a lower material cost. The obtained structure is mainly composed of tempered troostite and tempered bainite, with a small amount of ferrite and fused troostite. Compared with traditional pearlite steel or bridge cable steel wire rod with high troostitization rate, the tempered troostite of the present invention retains the characteristics of finer interlamellar spacing and higher strength of troostite than pearlite. After tempering and transformation to micro-spheroidized structure, it can take into account strength, effectively reduce tissue stress and dislocation density, and avoid pull hardening. Compared with the traditional method of treating bainite structure as It is an abnormal structure. The present invention contains a part of tempered bainite structure. The tempered bainite structure retains the high-strength characteristic of bainite. After tempering, a strong and tough structure is obtained, thereby improving the matrix strength, which can make up for the strength loss caused by reducing the carbon content and eliminating the alloy. At the same time, the plasticity of the wire rod is significantly improved by regulating the tempering state, which is more convenient for manufacturing into small-sized wire rods, so as to reduce the area reduction rate during the drawing process to the target diameter of the bridge cable, or it is not easy to break even in the deep drawing process, which is beneficial to improving the yield rate and the manufacturing efficiency of the bridge cable.
[0030] In a preferred embodiment, the interlamellar spacing of the tempered bainite is 85~110nm. When the interlamellar spacing of the tempered bainite becomes finer and the proportion of tempered bainite decreases, the strength of the wire rod increases and the plasticity decreases. Conversely, when the interlamellar spacing increases and the proportion of tempered bainite decreases, the strength of the wire rod decreases and the plasticity increases.
[0031] In a preferred embodiment, the network carbide level of the hot-rolled carbon wire rod is level 0, which can effectively eliminate the adverse effect of high carbon steel segregation on the wire rod caused by the increase of network carbides and improve the uniformity of the structure.
[0032] In a preferred embodiment, the mechanical property difference of the hot-rolled carbon wire rod is ≤20MPa. The increase in carbon content will aggravate the fluctuation of mechanical properties. The mechanical property difference of the wire rod can be effectively reduced by regulating the uniformity of the structure, which is beneficial to reducing the risk of wire breakage in the subsequent wire drawing process.
[0033] In a preferred embodiment, the diameter of the hot-rolled carbon wire rod is 12.5~15.0mm, and the finished product has high comprehensive mechanical properties, a tensile strength of 1140~1190MPa, and a cross-sectional shrinkage rate of 50%~56%, which significantly improves the plasticity of the wire rod without excessively deteriorating the strength of the wire rod. The smaller wire rod diameter facilitates obtaining the target bridge cable wire diameter through deep drawing, and can be used to manufacture 1670MPa-grade bridge cables through pickling, wire drawing, galvanizing and torsion.
[0034] Compared with the prior art, the beneficial effects of the present invention are at least:
[0035] (1) In view of the current situation that 1670MPa-class wire rods for bridge cables are usually produced at high speed by Stelmor air-cooling lines, but due to its limited cooling control capacity, it is often difficult to control the uniformity of the wire rod structure. At the same time, changes in the fan air volume will also increase the risk of abnormal structures such as martensite, resulting in an increased risk of wire breakage during the wire drawing process. The present invention combines the design of carbon chemical composition with online molten salt weak quenching isothermal technology to promote the wire rod to quickly enter the mixed phase region of the troostite phase region and the bainite phase region in the high-temperature austenite state, thereby inhibiting the three The secondary cementite refines the cementite carbides to form a mixed structure mainly composed of troostite and bainite, making the phase change of troostite and bainite more controllable, and then undergoes a long period of isothermal treatment to promote isothermal tempering of troostite and bainite structures, micro-spheroidization of part of the troostite structure, and uses roller slow cooling to further promote tempering and softening of the matrix structure, which can effectively avoid the risk of abnormal structures such as martensite produced by C elements, maximize the strengthening effect of carbon elements, improve the plasticity and organizational uniformity of the wire rod, adjust the strength and plasticity matching of the wire rod, and has good industrial adaptability.
[0036] (2) In view of the current situation that the cost of existing 1670MPa grade wire rod materials for bridge cables is high and the plasticity and microstructure uniformity are insufficient, the present invention is based on the high carbon carbon component of C-Si-Mn, and does not add strong hardenability components such as Cr and B, and microalloy components such as V and Ti. The material cost is lower, and the microstructure type is a mixed structure composed of tempered troostite, tempered bainite, ferrite, and fused troostite. The strong and tough organizational state can make up for the strength loss caused by reducing the carbon content and eliminating the alloy. The tempered state can effectively improve the plasticity of the wire rod, adjust the strength and plasticity matching of the wire rod, and improve the microstructure uniformity. The product has a tensile strength of 1140~1190MPa, a cross-sectional shrinkage rate of 50~56%, and a mechanical property circle difference of ≤20MPa. It is used in the manufacture of 1670MPa grade bridge cables and other application fields, can reduce the risk of wire breakage and torsional fracture in deep drawing, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0038] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0039] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0040] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0041] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional shrinkage rate, and the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0042] A preferred embodiment of the manufacturing method of the 1670MPa grade bridge cable with high plasticity hot-rolled carbon wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.7%, Si: 0.3%, Mn: 0.72%, P: 0.013%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0043] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet with rollable plasticity. After the steel billet comes out of the heating furnace, high-pressure initial rolling descaling water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter specification of 12.5mm through a rolling line. The rapid rolling and grain refinement are controlled by appropriate rolling temperature and reduction distribution. Specifically: the initial rolling descaling water pressure after the steel billet comes out of the heating furnace is controlled to be 19MPa, the initial rolling temperature is 1050℃, the initial rolling reduction is 36%, the intermediate rolling temperature is 960℃, the intermediate rolling reduction is 30%, the final rolling entrance is 910℃, and the final rolling deformation is 35%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The appropriate wire-spinning temperature is used to create conditions for the deformation nucleus of the sorbite phase. Specifically: the wire-spinning temperature is controlled to be 890℃.
[0044] The online molten salt weak quenching isothermal treatment adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers, and is quickly cooled to the molten salt temperature for online molten salt weak quenching isothermal treatment, so that the wire rod is cooled to a mixed phase region of the troostite phase region and the bainite phase region at a cooling rate of 35°C / s, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, promoting the transformation of high-temperature austenite structure to form a mixed structure mainly composed of troostite and bainite, and then carrying out long-term isothermal treatment to promote isothermal tempering of troostite and bainite structures, micro-spheroidization of part of the troostite structure, and adjusting the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 450°C, the processing time is 450s, the molten salt circulation volume is 600t / h, and the molten salt temperature rise is ≤9°C.
[0045] The roller slow cooling process is closed by a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment, so as to further promote the tempering and softening of the matrix structure and the micro-spheroidization of some structures. Specifically: the wire rod is conveyed through the heat preservation cover at a roller speed of 0.2 m / s, and the hot air above the salt bath tank is passed into the heat preservation cover, so that the wire rod is slowly cooled to 350°C at a cooling rate of 0.2°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage, and its metallographic structure diagram is as follows Figure 1As shown, the microstructure is tempered troostite + tempered bainite + ferrite + fused troostite, the network carbide level is level 0, the mechanical property difference is 17MPa, the tensile strength is 1179MPa, and the section reduction rate is 52%.
[0046] Comparative Example 1:
[0047] A method for manufacturing hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor strong air cooling → Stelmor weak air cooling, specifically: the initial rolling temperature is controlled to be 1005°C, the intermediate rolling temperature is 905°C, the final rolling entrance is 845°C, and the spinning temperature is 820°C; the Stelmor strong air cooling adopts an air volume of 200,000 m per fan 3 / h, open 1~6# fans at 95%, and cool the wire rod to 590℃ at a cooling rate of 9.5℃ / s. The Stelmore weak air cooling adopts an air volume of 200,000m 3 / h, open 7~11# fans at 25%, cool the wire rod to 350℃ at a cooling rate of 3.5℃ / s, and obtain the finished wire rod after it comes off the line. The microstructure is 82% troostite + 18% ferrite by volume, the network carbide grade is 1, the mechanical property difference is 65MPa, the tensile strength is 1080MPa, and the cross-sectional shrinkage rate is 35%.
[0048] It can be seen from the comparison results of Example 1 and Comparative Example 1 that compared with reducing the alloy content or eliminating the alloy component, there will be a significant loss of strength. The Stelmor air-cooled line performs high-speed production, and the air-cooling control capacity is limited. The precipitation of tertiary cementite along the crystal increases, increasing the risk of abnormal tissues such as martensite, and it will be difficult to regulate the uniformity of the wire rod tissue. Finally, the wire rod has higher residual stress and density dislocation inside, insufficient plasticity, and large difference in mechanical properties. The present invention combines the carbon chemical composition design with the online molten salt weak quenching isothermal technology to promote the wire rod to quickly enter the mixed phase zone of the troostite phase zone and the bainite phase zone in the high-temperature austenite state, which can inhibit tertiary cementite and avoid the risk of abnormal tissues such as martensite. The strong and tough tissue state can make up for the strength loss caused by reducing the carbon content and eliminating the alloy. The tempered state effectively improves the plasticity of the wire rod, adjusts the strength and plasticity matching of the wire rod, improves the uniformity of the tissue, and significantly reduces the difference in mechanical properties.
[0049] Comparative Example 2:
[0050] A method for manufacturing a hot-rolled carbon wire rod, which differs from Example 1 in that: the initial rolling temperature is controlled to be 1020°C, the intermediate rolling temperature is controlled to be 940°C, the final rolling entrance is controlled to be 880°C, the spinning temperature is controlled to be 860°C, the wire rod is cooled at a cooling rate of 30°C / s during online molten salt weak quenching isothermal treatment, and a finished wire rod is obtained after it comes off the line. Embodiment 2:
[0051] A preferred embodiment of the manufacturing method of the 1670MPa grade bridge cable with high plasticity hot-rolled carbon wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.74%, Si: 0.35%, Mn: 0.8%, P: 0.012%, S: 0.015%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0052] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet with rollable plasticity. After the steel billet comes out of the heating furnace, high-pressure initial rolling descaling water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 15mm through a rolling line. The rapid rolling and grain refinement are controlled by appropriate rolling temperature and reduction distribution. Specifically: the initial rolling descaling water pressure after the steel billet comes out of the heating furnace is controlled to be 20MPa, the initial rolling temperature is 1090℃, the initial rolling reduction is 26%, the intermediate rolling temperature is 1010℃, the intermediate rolling reduction is 26%, the final rolling entrance is 940℃, and the final rolling deformation is 25%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The appropriate wire-spinning temperature is used to create conditions for the deformation nucleus of the sorbite phase. Specifically: the wire-spinning temperature is controlled to be 915℃.
[0053] The online molten salt weak quenching isothermal treatment adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers, and is quickly cooled to the molten salt temperature for online molten salt weak quenching isothermal treatment, so that the wire rod is cooled to a mixed phase region of the troostite phase region and the bainite phase region at a cooling rate of 34°C / s, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, promoting the transformation of high-temperature austenite structure to form a mixed structure mainly composed of troostite and bainite, and then carrying out long-term isothermal treatment to promote isothermal tempering of troostite and bainite structures, micro-spheroidization of part of the troostite structure, and adjusting the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 490°C, the processing time is 750s, the molten salt circulation volume is 550t / h, and the molten salt temperature rise is ≤9°C.
[0054] The roller slow cooling process is closed with a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment, so as to further promote the tempering and softening of the matrix structure and the micro-spheroidization of some structures. Specifically: the wire rod is conveyed through the heat preservation cover at a roller speed of 0.5 m / s, so that the wire rod is slowly cooled to 325°C at a cooling rate of 0.5°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0055] Comparative Example 3:
[0056] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 2 in that the molten salt temperature is 425°C during the online molten salt weak quenching isothermal treatment, and the finished wire rod is obtained after the line is off.
[0057] Comparative Example 4:
[0058] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 2 in that the molten salt temperature is 525°C during the online molten salt weak quenching isothermal treatment, and the finished wire rod is obtained after the line is off. Embodiment 3:
[0059] A preferred embodiment of the manufacturing method of the 1670MPa grade bridge cable with high plasticity hot-rolled carbon wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.72%, Si: 0.43%, Mn: 0.65%, P: 0.012%, S: 0.015%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0060] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet with rollable plasticity. After the steel billet comes out of the heating furnace, high-pressure initial rolling descaling water is used to remove the oxide scale on the surface of the steel billet. Then, the steel billet is rolled into a wire with a diameter of 13.5mm through a rolling line. The rapid rolling and grain refinement are controlled by appropriate rolling temperature and reduction distribution. Specifically, the initial rolling descaling water pressure after the steel billet comes out of the heating furnace is controlled to be 18MPa, the initial rolling temperature is 1065℃, the initial rolling reduction is 32%, the intermediate rolling temperature is 980℃, the intermediate rolling reduction is 29%, the final rolling entrance is 920℃, and the final rolling deformation is 32%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism. The wire rod is spread on the roller and transported along the roller. The appropriate wire-spinning temperature is used to create conditions for the deformation nucleus of the sorbite phase. Specifically, the wire-spinning temperature is controlled to be 900℃.
[0061] The online molten salt weak quenching isothermal treatment adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers, and is quickly cooled to the molten salt temperature for online molten salt weak quenching isothermal treatment, so that the wire rod is cooled to a mixed phase region of the troostite phase region and the bainite phase region at a cooling rate of 33°C / s, the peak precipitation of tertiary cementite is suppressed, the cementite carbide is refined, and the high-temperature austenite structure is promoted to transform into a mixed structure mainly composed of troostite and bainite, and then a long time of isothermal treatment is carried out to promote isothermal tempering of the troostite and bainite structures, micro-spheroidization of part of the troostite structure, and adjust the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 476°C, the processing time is 690s, the molten salt circulation volume is 500t / h, and the molten salt temperature rise is ≤9°C.
[0062] The roller slow cooling process is closed with a heat preservation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers into the heat preservation cover for slow cooling treatment, so as to further promote the tempering and softening of the matrix structure and the micro-spheroidization of some structures. Specifically: the wire rod is conveyed through the heat preservation cover at a roller speed of 0.35m / s, so that the wire rod is slowly cooled to 330°C at a cooling rate of 0.4°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0063] Comparative Example 5:
[0064] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time during online molten salt weak quenching isothermal treatment is 400s, and a finished wire rod is obtained after going offline.
[0065] Comparative Example 6:
[0066] A method for manufacturing a hot-rolled carbon wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time during online molten salt weak quenching isothermal treatment is 815s, and a finished wire rod is obtained after going offline. Embodiment 4:
[0067] A preferred embodiment of the manufacturing method of the 1670MPa grade bridge cable with high plasticity hot-rolled carbon wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.69%, Si: 0.45%, Mn: 0.74%, P: 0.015%, S: 0.013%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0068] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet with rollable plasticity. After the steel billet comes out of the heating furnace, high-pressure initial rolling descaling water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter specification of 14mm through a rolling line. The rapid rolling and grain refinement of the structure are controlled by appropriate rolling temperature and reduction distribution. Specifically: the initial rolling descaling water pressure after the steel billet comes out of the heating furnace is controlled to be 19MPa, the initial rolling temperature is 1075℃, the initial rolling reduction is 28%, the intermediate rolling temperature is 995℃, the intermediate rolling reduction is 27%, the final rolling entrance is 930℃, and the final rolling deformation is 28%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The appropriate wire-spinning temperature is used to create conditions for the deformation nucleus of the sorbite phase. Specifically: the wire-spinning temperature is controlled to be 910℃.
[0069] The online molten salt weak quenching isothermal treatment adopts a salt bath tank with molten salt inside. The wire rod after spinning is conveyed through the salt bath tank by rollers, and is quickly cooled to the molten salt temperature for online molten salt weak quenching isothermal treatment, so that the wire rod is cooled to a mixed phase region of the troostite phase region and the bainite phase region at a cooling rate of 36°C / s, inhibiting the peak precipitation of tertiary cementite, refining cementite carbides, promoting the transformation of high-temperature austenite structure to form a mixed structure mainly composed of troostite and bainite, and then carrying out long-term isothermal treatment to promote isothermal tempering of troostite and bainite structures, micro-spheroidization of part of the troostite structure, and adjusting the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 460°C, the processing time is 580s, the molten salt circulation volume is 640t / h, and the molten salt temperature rise is ≤9°C.
[0070] The roller slow cooling process is closed with an insulation cover, and the wire rod coming out of the salt bath tank is conveyed by rollers to enter the insulation cover for slow cooling treatment, so as to further promote the tempering and softening of the matrix structure and the micro-spheroidization of some structures. Specifically: the wire rod is conveyed through the insulation cover at a roller speed of 0.25m / s, and the hot air above the salt bath tank is passed into the insulation cover, so that the wire rod is slowly cooled to 335°C at a cooling rate of 0.3°C / s until it is coiled; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled carbon wire rod product is obtained after packaging and storage.
[0071] The structure and performance of the wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were tested, and the comparison results obtained are shown in Table 1 below:
[0072] Table 1. Comparison of the microstructure and properties of different wire rod compositions and manufacturing methods
[0073]
[0074] It can be seen from the results of Examples 1 to 4 that the present invention is based on a high-carbon carbon component of C-Si-Mn, and the microstructure type is a mixed structure composed of tempered troostite, tempered bainite, ferrite, and fused troostite. The product has a tensile strength of 1140 to 1190 MPa, a cross-sectional shrinkage of 50 to 56%, and a mechanical property difference of ≤20 MPa. It is used in the manufacture of 1670 MPa-level bridge cables and other application fields, and can reduce the risk of wire breakage and torsional fracture during deep drawing.
[0075] From the comparison results of Example 1 and Comparative Example 2, it can be seen that appropriately increasing the spinning temperature can avoid the limitation of low-temperature spinning on low-temperature rolling, promote the homogenization of wire rod composition, reduce the load on the rolling mill and the deformation resistance of the wire, which is beneficial to the nucleation of troostite and makes the spacing between tempered troostite lamellae finer.
[0076] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature and the longer the treatment time, the temperature shifts toward the bainite peak phase transformation temperature, the proportion of tempered bainite in the wire rod increases, the proportion of tempered bainite decreases, the strength of the wire rod increases, and the plasticity decreases. However, if the molten salt temperature is too low, it is not conducive to the bainite transformation and isothermal tempering. Insufficient plasticity will cause wire breakage during drawing, and the torsional performance of the steel wire is difficult to guarantee.
[0077] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature and the longer the treatment time, the temperature shifts toward the troostite peak phase transformation temperature, which can provide more thermal power for isothermal tempering, increase the proportion of tempered troostite in the wire rod, and decrease the proportion of tempered bainite, reduce the strength of the wire rod, and increase the plasticity. However, the molten salt temperature is too high, which is not conducive to the bainite phase transformation or even the formation of troostite with finer interlamellar spacing and the control of ferrite formation. The strength of the wire rod is excessively deteriorated, and a larger area reduction rate is required for drawing and strengthening, which is not conducive to reducing the risk of wire breakage during drawing and achieving the final performance level of the bridge cable.
[0078] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the treatment time of the online molten salt weak quenching isothermal treatment is too short, and the austenite structure is not fully transformed, which is not conducive to the control of abnormal structure and matrix softening, resulting in insufficient softening of the wire rod and an increase in the difference in mechanical properties. From the comparison results of Example 3 and Comparative Example 6, it can be seen that the treatment time of the online molten salt weak quenching isothermal treatment is too long, the energy consumption is increased and the wire rod is too softened, which is not conducive to efficient production and matrix strength.
[0079] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the high temperature state of the wire rod can be continued by performing online molten salt weak quenching isothermal treatment and then slow cooling on a roller, and the slow cooling treatment can be further used to promote the tempering softening of the matrix structure and the micro-spheroidization of part of the structure, and finally achieve the control of the wire rod structure and the matching of strength and plasticity.
[0080] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention, and they are not intended to limit the scope of protection of the present invention. For example, the steel billet is obtained by sequentially performing converter smelting, refining, and continuous casting processes. Any equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables, characterized in that: The manufacturing method comprises: rolling a wire rod according to the chemical composition of a hot-rolled carbon wire rod, wherein the chemical composition and mass percentage of the hot-rolled carbon wire rod include: C: 0.69% to 0.74%, Si: 0.3% to 0.45%, Mn: 0.65% to 0.8%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥890°C, it is subjected to an online molten salt weak quenching isothermal treatment, so that the wire rod is cooled at a cooling rate of ≥33°C / s to a mixed phase of a troostite phase region and a bainite phase region zone, forming a mixed structure mainly composed of troostite and bainite and undergoing isothermal tempering transformation, and finally undergoing roller slow cooling to obtain a hot-rolled carbon wire rod with a microstructure including 47% to 53% by volume of tempered troostite, 40% to 46% by volume of tempered bainite, and the rest being a mixed structure composed of ferrite and fused troostite; the molten salt temperature of the online molten salt weak quenching isothermal treatment is 450 to 490°C, the treatment time is 450 to 750s, and the roller slow cooling controls the wire rod to be cooled at a cooling rate of 0.2 to 0.5°C / s until it is coiled.
2. The method for manufacturing the 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling descaling water pressure after the steel billet leaves the heating furnace is controlled to be ≥18MPa.
3. The method for manufacturing the 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: The initial rolling temperature is 1050~1090℃, the initial rolling reduction is 26%~36%, the intermediate rolling temperature is 960~1010℃, the intermediate rolling reduction is 26%~30%, the final rolling entrance is 910~940℃, and the final rolling deformation is 25%~35%.
4. The method for manufacturing a 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation rate of the online molten salt weak quenching isothermal treatment is 500-640 t / h, and the molten salt temperature rise is ≤9°C.
5. The method for manufacturing the 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling adopts closing the heat preservation cover and conveying the wire rod into the heat preservation cover at a roller speed of 0.2-0.5m / s.
6. A 1670MPa grade high plasticity hot rolled carbon wire rod for bridge cables, characterized in that: The hot-rolled carbon wire rod is manufactured according to the manufacturing method of the 1670MPa grade high-plasticity hot-rolled carbon wire rod for bridge cables according to any one of claims 1 to 5.
7. The 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 6, characterized in that: The interlamellar spacing of the tempered bainite is 85-110 nm, the network carbide grade of the hot-rolled carbon wire rod is grade 0, and the mechanical property difference is ≤20 MPa.
8. The 1670MPa grade high plasticity hot-rolled carbon wire rod for bridge cables according to claim 6, characterized in that: The hot-rolled carbon wire rod has a diameter of 12.5-15.0 mm, a tensile strength of 1140-1190 MPa, and a cross-sectional shrinkage of 50%-56%.
Citation Information
Patent Citations
Coil rod used for 1670MPa level bridge cable zinc-coated wire and preparation method of coil rod
CN102181786A
Manufacturing method of 9.8-grade non-adjusted cold forging steel high-strength hot-rolled wire rod
CN118166191A
Cold forging steel high-carbon carbon wire rod for 14.9-grade bolt and manufacturing method of cold forging steel high-carbon carbon wire rod
CN118621220A